Breaking Through Resistance: Carbapenem-Resistant Nocardia?!—A Case Report - Vlad-Sabin Ivan; Paul-Gabriel Ciubotaru; Liviu Cirin; Florin Giru; Dan Costachescu; Daniel-Florin Lighezan; Roxana Buzas (Medicina)
Nocardia is an emerging bacterial disease that often affects patients with compromised immune systems. As the number of patients undergoing solid organ transplants continues to rise, and as more cancer survivors are treated with long-term immune-modifying agents, corticosteroids, and immunosuppressive medications, organisms that typically pose no harm are becoming a public health concern. Carbapenems are usually a second-line therapy in the setting of Nocardia infections. We present the case of a patient who had an immunocompromised status and was diagnosed with Nocardia farcinica, which showed in vitro resistance to carbapenems. The symptoms were non-specific and had a common presentation with headache, fatigue, and a nonresponsive cough to usual cough drugs, although the infection was disseminated and had severe CNS and ocular involvement. The clinical course worsened when the carbapenem was withdrawn and markedly improved when it was re-administered, although the initial antibiogram showed resistance to carbapenems. Despite the observed in vitro resistance in the laboratory, the re-administration of carbapenems was beneficial, as both inflammatory markers and clinical status showed improvement. This was based on clinical judgment, which carefully evaluated the associated risks and benefits. Also, this raises the question of potential risks to develop real resistance to carbapenems of some Nocardia species, which could pose a significant challenge to healthcare. It could become a serious healthcare problem in the future and should prompt active environmental testing.